(untitled) (Actualizaciones en Sida e Infectología, 2023)
Introduction: For people living with Human Immunodeficiency Virus (PLHIV), metabolic deregulations have been described, which could be related to a higher cardiovascular risk. Objective: To assess the epicardial adipose tissue thickness (EATT), and the relationship between this value and clinical and biochemical parameters of cardiovascular risk in adults living with HIV, if compared to a healthy control group. Methods: Observational, with prospective inclusion. It included PLHIV >18 years and seronegative controls. All of them had their EAT measured in two axes by transthoracic echocardiogram, as well as the carotid intima-media thickness determined by color doppler ultrasound. Results: 75 patients, 58.7% male, age of 36 years (RIQ 22). 50.7% patients with HIV (CD4+ of 512 cells/mm3; and 80% undetectable). BMI was of 25.2 kg/m2 and waist circumference of 88.5 cm, without between-groups differences. PLHIV had lower HDL, higher C reactive protein, higher D-dimer and higher fasting blood glucose. EATT was higher in PLHIV (4.05 vs 3.49 mm, p=0.021), and this correlated with age, fasting blood glucose and D-dimer. In PLHIV, it correlated with insulinemia, HOMA2- IR index, HDL-c ; and D-dimer. Treatment with Efavirenz was associated with a higher EATT. Conclusion: PLHIV presented increased systemic inflammation of low grade and higher EATT than the seronegative control group. EATT was associated in PLHIV to insulin resistance.